2006
DOI: 10.1007/s00440-006-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Penalties for Gaussian Model Selection

Abstract: This paper is mainly devoted to a precise analysis of what kind of penalties should be used in order to perform model selection via the minimization of a penalized least-squares type criterion within some general Gaussian framework including the classical ones. As compared to our previous paper on this topic (Birgé and Massart in J. Eur. Math. Soc. 3, 203-268 (2001)), more elaborate forms of the penalties are given which are shown to be, in some sense, optimal. We indeed provide more precise upper bounds for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
344
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(357 citation statements)
references
References 39 publications
13
344
0
Order By: Relevance
“…Simulations discussed in the Supplementary Material show that the mirror penalty detects the degree of sparsity automatically. It can be shown that for n 1 larger than that degree, the mirror penalty ν(n 1 ) increases faster than the lower bound of Birgé and Massart (2007). Unlike that lower bound, however, the mirror paradigm is not limited to normal errors or to Mallows' C p criterion.…”
Section: The Mirror and Other Penaltiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Simulations discussed in the Supplementary Material show that the mirror penalty detects the degree of sparsity automatically. It can be shown that for n 1 larger than that degree, the mirror penalty ν(n 1 ) increases faster than the lower bound of Birgé and Massart (2007). Unlike that lower bound, however, the mirror paradigm is not limited to normal errors or to Mallows' C p criterion.…”
Section: The Mirror and Other Penaltiesmentioning
confidence: 99%
“…The mirror corrected penalty can be compared to the minimum penalty for consistent estimators (Birgé and Massart, 2007). Being a lower bound, that penalty is not data-specific, unlike that proposed in this paper.…”
Section: The Mirror and Other Penaltiesmentioning
confidence: 99%
See 3 more Smart Citations